Full-scale fire test on an earthquake-damaged reinforced concrete frame. (April 2015) - Kamath, Praveen; Sharma, Umesh Kumar; Kumar, Virendra; Bhargava, Pradeep; Usmani, Asif; Singh, Bhupinder; Singh, Yogendra; Torero, Jose; Gillie, Martin; Pankaj, Pankaj
Abstract: Fire, in the aftermath of an earthquake has evolved as a severely destructive force since the last century[1] . Codes and regulations exist in countries situated in seismically active regions of the world in order to ensure safety of buildings and their occupants in the event of an earthquake; it is however rare to find regulations that also require the consideration of fire following an earthquake, thereby leaving this possibility to be dealt with entirely by emergency responders on an ad-hoc basis with little preparedness. Fire following earthquake (FFE) events in the past, although rare, have sometimes been as destructive as the original earthquake. The aim of this study was to carry out a set of full-scale loading tests on an earthquake damaged, reinforced concrete frame subsequently exposed to fire. The sequential loading was devised in the form of a three phase testing procedure – simulated earthquake loading facilitated by cyclic quasi-static lateral loads; followed by a compartment fire; and finally by subjecting the earthquake and fire damaged frame to a monotonic pushover loading to assess its residual capacity. The reinforced concrete frame was well instrumented with numerous sensors, consisting of thermocouples, strain gauges, linear variable differential transducers (LVDTs) and pressure sensors. A large database of results consisting of temperature profiles, displacements and strains has been generated and salient observations have been made during each stage of loading. This paper describes the experimental investigation and serves as a vehicle for dissemination of the key findings and all the important test data to the engineering community which could be used for validating numerical simulations for further advancing the knowledge and understanding in this relatively poorly researched area. Highlights: Full scale test on earthquake damaged reinforced concrete structures in fire. The study investigates the performance of earthquake damaged RC frame in compartment fire. Observations from the simulated seismic loading tests were contrary to FEMA 356 provisions. We report a non-uniform distribution of temperatures throughout the compartment. The seismic provisions of the Indian Standards are beneficial to provide a better fire resistance to RC structures.